Exploration on the origin of enhanced piezoelectric properties in transition-metal ion doped KNN based lead-free ceramics. Issue 14 (1st October 2018) - Xu, Fang; Chen, Jian; Lu, Yinmei; Zhang, Qingfeng; Zhang, Qi; Zhou, Taosheng; He, Yunbin
Abstract: In this work, we studied effects of Ni2 O3 and Co2 O3 doping on crystal structures, microstructures, orthorhombic and tetragonal phase transition temperature ( T o-t ), and electrical properties of [Li0.06 (Na0.57 K0.43 )0.94 ][Ta0.05 (Sb0.06 Nb0.94 )0.95 ]O3 (LNKTSN) lead-free ceramics. The experimental results showed that the Ni2 O3 addition with appropriate amount could shift the T o-t downwards to the room temperature, and thus obviously increasing the room-temperature piezoelectric coefficient ( d 33 ), dielectric coefficient ( ε r ) and electromechanical coupling coefficient ( k p ) of the LNKTSN ceramics. These were consistent with previous experimental results obtained in Fe2 O3 doped LNKTSN ceramics. On the contrary, Co 3+ doping shifted continuously the T o-t upward and deteriorated obviously piezoelectric properties of LNKTSN ceramics. Fe, Co and Ni had similar ion radii and were expected to result in the same (donor or acceptor) doping effects on electrical properties of LNKTSN ceramics. The different doping effects between Co 3+ (deterioration) and Ni 3+ or Fe 3+ (improvement) on the electrical properties of LNKTSN ceramics suggested that the coexistence of orthorhombic and tetragonal phases at room temperature due to downward shift of T o-t, rather than ion doping (donor or acceptor doping) effects was the main cause for enhanced room-temperature piezoelectric properties. This conclusion can be extended to all KNN-based materials in general, thus offering principle guide for future development of new lead-free materials with good piezoelectric properties.